2022
DOI: 10.1155/2022/6489923
|View full text |Cite
|
Sign up to set email alerts
|

Aβ1–40 Oligomers Trigger Neutrophil Extracellular Trap Formation through TLR4- and NADPH Oxidase-Dependent Pathways in Age-Related Macular Degeneration

Abstract: Neutrophils participate in the advancement of the human innate immune system and respond to perceived endogenous and exogenous threats. As a response mechanism, neutrophil extracellular traps (NETs) form near pathogens and surrounding tissues during an immune response. Drusen is an important marker of Age-Related Macular Degeneration (AMD) and plays an important role in the course of AMD. Aβ1-40 is the main component of drusen. However, the relationship between NETs and AMD or Aβ1-40 is unclear. Here, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…Recent research has uncovered evidence of ETs and their involvement in the pathophysiology of ocular diseases, including diabetic retinopathy, uveitis, and AMD (14, 15, 140). Relevant to our findings, Chen et al demonstrated that the amyloid β-protein Aβ1-40, the primary component of drusen, triggers the release of ETs through the activation of pro-inflammatory pathways (141). Their findings also demonstrated that PAD4 inhibitors effectively alleviate PL infiltration in the retina and, thus, chronic inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…Recent research has uncovered evidence of ETs and their involvement in the pathophysiology of ocular diseases, including diabetic retinopathy, uveitis, and AMD (14, 15, 140). Relevant to our findings, Chen et al demonstrated that the amyloid β-protein Aβ1-40, the primary component of drusen, triggers the release of ETs through the activation of pro-inflammatory pathways (141). Their findings also demonstrated that PAD4 inhibitors effectively alleviate PL infiltration in the retina and, thus, chronic inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…Recent research has uncovered evidence of ETs and their involvement in the pathophysiology of ocular diseases, including diabetic retinopathy, uveitis, and AMD [ 14 , 15 , 146 ]. Relevant to our findings, Chen et al demonstrated that the amyloid β-protein Aβ1-40, the primary component of drusen, triggers the release of ETs through the activation of pro-inflammatory pathways [ 147 ]. Their findings also demonstrated that PAD4 inhibitors effectively alleviate PL infiltration in the retina and, thus, chronic inflammation.…”
Section: Discussionsupporting
confidence: 84%
“…Neutrophil extracellular trap formation has previously been associated with retinal diseases (Ghosh et al, 2019;Wang et al, 2018). Aβ1-40 the main amyloidbeta component of the drusen characteristic of AMD may promote neutrophil extracellular trap formation in AMD through the Toll-like receptor 4 and neutrophil NADPH oxidase pathways (Chen et al, 2022). PAD4 inhibition in the mouse model led to reduced neutrophil extracellular trap formation, providing a potential therapeutic option for AMD (Chen et al, 2022).…”
Section: Neutrophilsmentioning
confidence: 96%
“…Aβ1-40 the main amyloidbeta component of the drusen characteristic of AMD may promote neutrophil extracellular trap formation in AMD through the Toll-like receptor 4 and neutrophil NADPH oxidase pathways (Chen et al, 2022). PAD4 inhibition in the mouse model led to reduced neutrophil extracellular trap formation, providing a potential therapeutic option for AMD (Chen et al, 2022). PAD4 inhibition is currently used to treat rheumatoid arthritis and lupus, among other autoimmune diseases.…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation